PTH-104 Anti-tnf drug and antibody testing at week 30 in patients with inflammatory bowel disease: is it worthwhile?. (17th June 2017) - Boal, A; Squires, SI; Naismith, GD
Abstract : Introduction: Recent NICE guidelines recommend further research into the clinical outcomes of drug level and antibody testing (TDM) in anti-TNF therapy. The Royal Alexandra and Vale of Leven Hospitals introduced drug level and antibody testing as part of our assessment criteria for all patients receiving Infliximab (IFx) and Adalimumab (ADA). Following testing at 12 weeks, our results indicated that 16% of patients had sub-therapeutic or undetectable drug levels. This report aims to describe outcomes following additional testing at week 30 to determine the yield of abnormal results. Method: Drug and antibody levels were sub-categorised to identify patients with drug levels greater than or equal to 3 µg/mL (therapeutic), less than 3 µg/mL but greater than 0.8 µg/mL (subtherapeutic) and less than 0.8 µg/mL (undetectable) All patients were anti-TNF naïve at commencement. Patients with therapeutic levels at week 12 were prospectively planned to have additional drug levels carried out at week 30, in addition to symptom assessment. Results: 45 'Week 30' TDM measurements were available at the time of this report (40 ADA and 5 IFx) 40/45 (89%) (38 ADA and 2 IFx) continued to have therapeutic drug levels. 1/40 (3%) had positive antibodies. 36/40 (90%) were asymptomatic. 4/40 (10%) reported symptoms which prompted further investigation confirmed active disease and 4/4 commenced alternative biological therapy. 4/45 (9%) had subtherapeutic drug levels. There was no antibody formation (0/4). 2/4 (50%) were on ADA and it was suspected that these levels reflected lack of adherence. 2/4 (50%) on IFx had drug therapy increased to 10 mg/kg dosage as per local protocol. 1/45 (2%) (IFx) had undetectable drug and positive antibodies. Active disease was confirmed on investigation and an alternative biological therapy was commenced. Conclusion: Despite therapeutic TDM measurements at week twelve, 11% percent of those patients had abnormal levels at week 30. This yield of abnormal results indicates that there appears to be benefit in carrying a week 30 test. Further work would be required to determine the optimal timing of TDM in such patients. Disclosure of Interest: None Declared